2006
DOI: 10.1007/s10555-006-8498-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targeting of the lymphovascular system for imaging and therapy

Abstract: Progress toward targeting cancer cells is a multi-disciplinary endeavor. In addition to the surgical and oncology specialties, radiologists collaborate with mathematicians, computer scientists, and physicists, in a constant effort to incrementally improve upon the current imaging modalities. Recently, radiologists have formed collaborations with molecular biologists and chemists in order to develop molecular agents that target cancer cells via receptor-substrate or specific physiochemical interactions. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…Experimental in vivo lymphangiography relies on the lymphatic uptake of molecules such as ferritin or FITC-dextran [4][5][6]. In clinical practice, lymphatic mapping employs the use of radiocolloid solutions or dyes [22,23]. While these strategies can provide information about lymphatic vessel density and function, they are transient and nonspecific, and do not yield information on real-time cancer cell trafficking through lymphatic networks.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental in vivo lymphangiography relies on the lymphatic uptake of molecules such as ferritin or FITC-dextran [4][5][6]. In clinical practice, lymphatic mapping employs the use of radiocolloid solutions or dyes [22,23]. While these strategies can provide information about lymphatic vessel density and function, they are transient and nonspecific, and do not yield information on real-time cancer cell trafficking through lymphatic networks.…”
Section: Discussionmentioning
confidence: 99%
“…6,22 Also, several studies have reported that chromolymphography, a well-known technique, provided excellent staining of retroperitoneal lymph nodes and facilitated nodal selectivity during lymphadenectomy. 7,8,11 Satoh and colleagues 6 reported that radio-guided mapping of sentinel lymph nodes (SLNs) with laparoscopy in humans was feasible, and nearly all SLNs were detected accurately by this procedure. They concluded that in the near future, the standard RPLND may be avoided in most patients with clinical stage I testicular carcinoma by using focused examination of SLNs.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] In our previous experimental study of rats, we demonstrated that both spermatic funicular and intratesticular injections of PBV dye are feasible and accurate methods for retroperitoneal lymph node mapping in rats. 12 In this pilot-feasibility study, we investigated whether spermatic funicular and intratesticular PBV dye injection is a feasible and accurate method for retroperitoneal lymph node mapping in pigs and whether this method can be helpful in visualizing retroperitoneal lymph nodes during laparoscopic RPLND.…”
Section: Introductionmentioning
confidence: 99%
“…This study was not powered to test for a significant difference in SLN accumulation between Lymphoseek and fTcSC. This is due to the extremely high variability in SLN uptake between subjects [8].…”
Section: Discussionmentioning
confidence: 99%